The Role Of Social And Psychological Support For Pregnant Women In Class II A Women's Correctional Institution, Semarang - Mitro Subroto; Desi Safitri (YUSTISIA MERDEKA : Jurnal Ilmiah Hukum, 2025)
Abstract Introduction to the Problem Pregnant women in correctional facilities face unique challenges that affect their well-being and rehabilitation process. Incarceration can lead to increased psychological distress, social isolation, and inadequate access to essential healthcare services, including prenatal and postnatal care. The role of social and psychological support in correctional facilities is crucial to ensuring the well-being of pregnant inmates and their unborn children. However, in many institutions, the implementation of these support systems remains insufficient due to resource constraints, lack of trained personnel, and overcrowding. This study examines the extent to which social and psychological support is provided to pregnant women in the Women's Correctional Facility Class II A Semarang and identifies challenges in implementing these programs. Purpose/Study Objectives This study aims to analyze the role of social and psychological support for pregnant women in correctional facilities by assessing the availability and effectiveness of existing support programs, identifying challenges in their implementation, and evaluating their alignment with legal frameworks such as Law No. 22 of 2022 and Law No. 18 of 2014. Additionally, this research seeks to provide recommendations for improving social and psychological support in correctional settings, ensuring that pregnant inmates receive adequate care and assistance during their incarceration. Design/Methodology/Approach A qualitative research approach was employed to explore the experiences of pregnant women in correctional facilities and the implementation of support programs. Data were collected through in-depth interviews with pregnant inmates and correctional staff to understand their perspectives on social and psychological support. Observations were conducted within the correctional facility to assess the availability and quality of support services. Additionally, document analysis was performed on policies, regulations, and rehabilitation programs to evaluate their alignment with national legal frameworks and identify gaps in implementation. Findings The study found that social support is primarily provided through religious study groups and group counseling sessions, which help pregnant inmates cope with incarceration. However, psychological support remains limited due to a lack of trained staff and inadequate infrastructure. One of the main challenges in implementing these support systems is the limited availability of trained professionals, resulting in infrequent counseling sessions. Overcrowding within the facility also restricts access to private counseling and mental health services, making it difficult for inmates to receive individualized psychological care. Additionally, reproductive health services are infrequent, leading to inconsistent prenatal care for pregnant inmates. Furthermore, insufficient training for correctional staff results in a lack of understanding of the specific needs of pregnant women, further hindering the effectiveness of existing support programs. Although support programs align with legal regulations, their implementation remains suboptimal. To address these challenges, this study recommends increasing resource allocation to enhance support services, providing specialized training for correctional staff to better handle the needs of pregnant inmates, and improving facility infrastructure to create a more supportive environment. Strengthening these aspects will help ensure that pregnant women in correctional facilities receive the necessary social and psychological support to improve their well-being and rehabilitation outcomes. Paper Type: Research Article